Functional connectivity changes differ in early and late‐onset alzheimer's disease. Issue 7 (5th October 2013) - Gour, Natalina; Felician, Olivier; Didic, Mira; Koric, Lejla; Gueriot, Claude; Chanoine, Valérie; Confort‐Gouny, Sylviane; Guye, Maxime; Ceccaldi, Mathieu; Ranjeva, Jean Philippe
Abstract At a similar stage, patients with early onset Alzheimer's disease (EOAD) have greater neocortical but less medial temporal lobe dysfunction and atrophy than the late‐onset form of the disease (LOAD). Whether the organization of neural networks also differs has never been investigated. This study aims at characterizing basal functional connectivity (FC) patterns of EOAD and LOAD in two groups of 14 patients matched for disease duration and severity, relative to age‐matched controls. All subjects underwent an extensive neuropsychological assessment. Magnetic resonance imaging was used to quantify atrophy and resting‐state FC focusing on : the default mode network (DMN), found impaired in earlier studies on AD, and the anterior temporal network (ATN) and dorso‐lateral prefrontal network (DLPFN), respectively involved in declarative memory and executive functions. Patterns of atrophy and cognitive impairment in EOAD and LOAD were in accordance with previous reports. FC within the DMN was similarly decreased in both EOAD and LOAD relative to controls. However, a double‐dissociated pattern of FC changes in ATN and DLPFN was found. EOAD exhibited decreased FC in the DLPFN and increased FC in the ATN relative to controls, while the reverse pattern was found in LOAD. In addition, ATN and DLPFN connectivity correlated respectively with memory and executive performances, suggesting that increased FC is here likely to reflect compensatory mechanisms. Thus, large‐scale neural network changes in EOAD and LOAD endorse both common features and differences, probably related to a distinct distribution of pathological changes. Hum Brain Mapp 35:2978–2994, 2014. © 2013 Wiley Periodicals, Inc.